Innovation and Modernism in the Portuguese Tourist Film between the late 1950s and the early 1970s - Sampaio, S. (NECS 2014 Conference, ‘Creative Energies – Creative Industries’, 2014)
My paper draws on research conducted at the Portuguese Film Museum to address the innovations at the level of form and content that took place in the Portuguese tourist film between the late 1950s and the early 1970s. This corresponds to a period of modernisation of the Portuguese society and relative ‘liberalisation’ of the regime (which culminated in the ‘Marcelist Spring’, when Marcelo Caetano succeeded to Salazar as head of the government). The growing importance of consumer culture, which the tourist sector came to epitomise, together with innovations in the audio-visual field (the emergence of the ‘Novo Cinema’; the growing importance of television and advertising), favoured the renovation of the tourist film. As earlier focus on domestic tourism shifted to international tourism (by 1964, the number of international tourists had reached one million), the idea of the modern which these films conveyed took on new, politically ambivalent, meanings (Williams, 1989), worth investigating more closely.